Hypothalamic mTORC2 is essential for metabolic health and longevity. Issue 5 (1st August 2019) - Chellappa, Karthikeyani; Brinkman, Jacqueline A.; Mukherjee, Sarmistha; Morrison, Mark; Alotaibi, Mohammed I.; Carbajal, Kathryn A.; Alhadeff, Amber L.; Perron, Isaac J.; Yao, Rebecca; Purdy, Cole S.; DeFelice, Denise M.; Wakai, Matthew H.; et al.
Abstract: The mechanistic target of rapamycin (mTOR) is an evolutionarily conserved protein kinase that regulates growth and metabolism. mTOR is found in two protein complexes, mTORC1 and mTORC2, that have distinct components and substrates and are both inhibited by rapamycin, a macrolide drug that robustly extends lifespan in multiple species including worms and mice. Although the beneficial effect of rapamycin on longevity is generally attributed to reduced mTORC1 signaling, disruption of mTORC2 signaling can also influence the longevity of worms, either positively or negatively depending on the temperature and food source. Here, we show that loss of hypothalamic mTORC2 signaling in mice decreases activity level, increases the set point for adiposity, and renders the animals susceptible to diet‐induced obesity. Hypothalamic mTORC2 signaling normally increases with age, and mice lacking this pathway display higher fat mass and impaired glucose homeostasis throughout life, become more frail with age, and have decreased overall survival. We conclude that hypothalamic mTORC2 is essential for the normal metabolic health, fitness, and lifespan of mice. Our results have implications for the use of mTORC2‐inhibiting pharmaceuticals in the treatment of brain cancer and diseases of aging. Abstract : The hypothalamic activity of the protein kinase mTORC2 (mechanistic target of rapamycin complex 2) increases with age. Genetic disruption of hypothalamic mTORC2 leads to a lifelong increase in adiposity, as well as decreased spontaneous activity and increased frailty. Mice lacking hypothalamic mTORC2 have decreased lifespan. These findings demonstrate that hypothalamic mTORC2 is essential for the metabolic health, fitness, and lifespan of mice.